Is the Triage System Welcomed in the Tertiary Hospital of the Limpopo Province? A Qualitative Study on Patient's Perceptions - Thabo Arthur Phukubye; Tshepo Albert Ntho; Livhuwani Muthelo; Masenyani Oupa Mbombi; Mamare Adelaide Bopape; Tebogo Maria Mothiba (MDPI AG, 2023)
A triage system in the emergency department is necessary to prioritize and allocate scarce health resources to the medical needs of the patients to facilitate quality health service delivery. This paper aimed to ascertain if the triage system is welcomed in the tertiary hospital of Limpopo Province by exploring patients' perceptions in the emergency department in South Africa. A qualitative research approach was used in this study with descriptive, explorative, and contextual research design to reach the research objective. Purposive sampling was used to select the patients who participated in semi-structured one-on-one interviews, which lasted between 30 and 45 min. The sample size was determined by data saturation after 14 participants were interviewed. A narrative qualitative analysis method was used to interpret and categorize the patients' perceptions into seven domains of Benner's theory. The six relevant domains illustrated mixed patients' perceptions regarding the triage system in the emergency departments. The domain-helping role of the triage system was overweighed by the dissatisfaction of the needy patients who waited for an extended period to receive emergency services. We conclude that the triage system at the selected tertiary hospital is not welcomed due to its disorganization and patient-related factors in the emergency departments. The findings of this paper are a point of reference for reinforcing the triage practice and improved quality service delivery by the emergency department healthcare professionals and the department of health policymakers. Furthermore, the authors propose that the seven domains of Benner's theory can serve as a foundation for research and improving triage practice within emergency departments.